How institutional factors influence economic diversification of the Russian Arctic monoprofile towns: (the case of cities in Yamal Nenets Autonomous Okrug) - Alexander Pelyasov; Nadezhda Zamyatina (European Regional Science Association (ERSA), 2013)
This research is based on the materials collected during the preparation of the official Strategies of socio-economic development of two oil-producing cities in the south of Yamal-Nenets autonomous Okrug: Muravlenko and Gubkinsky. Our study shows that for the success of diversification not only financial but also institutional factors are important. The cities of Muravlenko and Gubkinskiy have the similarities in the time of their foundation (1984 and 1986), in population (33000 and 25000 inhabitants), in the volume of their municipal budget (3.9 and 3.3 billion Rubles in 2011 correspondingly), in decline of the oil production during the last decade. However, the trajectories of economic diversification of these cities do differ radically. The key factor generated these differences was the geographic location of these cities to sub-regional centre - the city of Noyabrsk: Muravlenko is situated by 120 km distance, Gubkinskiy ? by 240 km. This seemingly small geographic difference has resulted in a great difference of their institutional positions: Muravlenko has become an institutional periphery, and Gubkinskiy ? an independent subcenter. The key oil producing enterprise of Muravlenko was managed by the headquarters in Noyabrsk («Noyabrsk Neftegaz») up to 2008. The main oil producing enterprise of Gubkinsky initially was also governed from headquarters in Noyabrsk, but due to the inconvenience of management of geographically remote assets it became independent company in 1986 with a headquarter in Gubkinsky («Rosneft-Purneftegaz»). Institutional position resulted in the formation of the different relations of ownership and power: in Muravlenko a colonial model has been developed (real control over the local property and power came from Noyabrsk), in Gubkinsky an embedded model has been developed. In Muravlenko an authoritarian model of local government was formed. Its characteristic feature was the orientation on the interaction with counterparties in Noyabrsk combined with a minimum attention to the local community. In Gubkisky the more democratic model of local government has been developed. This is reflected, for example, in the number of public councils under the local government (17 in Muravlenko and 54 in Gubkinsky). The most important indicator of the orientation towards the local community was the authorities? attitude to small business: in Muravlenko support of small business was significantly fewer than in Gubkinsky (the budget expenditure on the development of small businesses in 2011 was, correspondingly, 100 and 1700 Rubles per one city resident). In Gubkinsky small business became an important tool of the diversification of this monoprofile city.
Keywords: 330; monoprofile Arctic cities; diversification of the local economy; institutional factors